Observações sobre compatibilidade no gênero brassica - Brune, Walter (Revista Ceres, 1949)
Several species and varieties of Brassica were interbred, for the purpose of studying their phylogenetic relationship. The index “seed: ovules” was adopted as a criterion te evaluate the compatibility among them. The fertility of the hybrids was studied by means of comparison with that of the parents. As as result of these studies, it was concluded that Br. chinensis, Br. pekinensis, and Br. rapa (varieties Rst and TR) seem to belong to the same taxonomic group, whereas Br. japonica seems to form part of another group considerably apart. Such conclusion received further support from the study of the compatibility between Br. oleracea and the above mentioned species. Br. japonica showed to be much closer to Br. oleracea than anyone of the other species studied. As illustration, the fertility of the hybrids Br. chinensis x Br. rapa, its reciprocal, and Br. pekinensis x Br. rapa was submitted to a genetic analysis, carried down to the second generation (Fy). The results seem to indicate the existence of a trimerous inheritance, in which the seli-fertility is condicioned by a triple dominance.